Autocatalytic synthesis of molecular-bridged silica aerogels with excellent absorption and super elasticity. Issue 111 (26th October 2015) - Wei, Yong; Wang, Jin; Zhang, Yulu; Wang, Lin; Zhang, Xuetong
Abstract : A catalyst-free approach to synthesize molecular-bridged silica aerogels with excellent absorption performance and super elasticity was proposed. Abstract : In this study, molecular-bridged silica aerogels (MBSAs) were synthesized via supercritical CO2 liquid drying of bridged 3-aminopropyltriethoxysilane (APTES) wet gels, which were autocatalytic gelled by the catalyst-free bridging of APTES and 1, 4-phthalaldehyde via a Schiff base condensation. The detailed mechanism of this facile, one-pot and autocatalytic approach for the production of MBSAs was revealed by in situ 1 H NMR and FTIR measurements, and the critical conditions for the successful autocatalytic gelation of the bridged-APTES were investigated. The densities and average pore diameters were in the range from 0.0535 to 0.0702 g cm −3 and from 12.9 to 14.1 nm, respectively. Moreover, the morphologies and thermal stability of the products were characterized by SEM and TGA, respectively. Interestingly, the MBSAs show excellent absorption performance for organic solvents, e.g., hexane, dichloromethane, kerosene, dimethylsulfoxide, tetrahydrofuran, ethanol, ethylsilicate, and N, N -dimethylformamide. Among those, 2437% by mass absorption of dichloromethane was achieved. Moreover, the absorption property of the aerogel was stable, with nearly no deterioration even after 30 absorption–desorption cycles. In addition, the aerogel showed remarkable flexibility, with the highest deformation of 90% and complete recovery after the release of stress, and it can be under through 30 cycles of compression–reversion process with 40% deformation.